The Implementation of Activity-Based Costing System in Determining the Price of Rooms at Swiss-Belhotel Rainforest - I W G Mahayasa; I M A Putrayasa; P Subiyanto (Journal of Applied Sciences in Accounting, Finance, and Tax, 2019)
This study aims to determine the selling price calculation room by using Activity Based Costing System and the magnitude comparison between the selling price of the rooms Traditional Cost Accounting System with Activity Based Costing System to determine a more accurate selling price. The analysis technique used in this study was a comparative descriptive with quantitative approach. Results from this study showed that the selling price calculation room with Activity Based Costing System produces a smaller cost than the Traditional Cost Accounting System.From the results of these calculations produce The excess on the type Deluxe Room as big as Rp70.753,00, type Grand Deluxe Room for Rp81.605,00, type Junior Suite Room as big as Rp125.846,00 and type Executive Suite Room as big as Rp131.874,00. Selling price difference is due to On Activity Based Costing System use a lot of cost driver so that the results are more accurate.